Natural history of pure autonomic failure: A United States prospective cohort. Issue 2 (23rd February 2017) - Kaufmann, Horacio; Norcliffe‐Kaufmann, Lucy; Palma, Jose‐Alberto; Biaggioni, Italo; Low, Phillip A.; Singer, Wolfgang; Goldstein, David S.; Peltier, Amanda C.; Shibao, Cyndia A.; Gibbons, Christopher H.; Freeman, Roy; Robertson, David; et al.
Abstract : Objective: To define the clinical features and biomarkers that predict which patients with pure autonomic failure will develop Parkinson disease, dementia with Lewy bodies, or multiple system atrophy. Methods: One hundred patients who presented with pure autonomic failure were recruited at 5 medical centers in the United States. Seventy‐four patients agreed to be followed prospectively. Patients underwent clinical evaluations including neurological rating scales, sleep questionnaires, smell test, and sympathetic and parasympathetic cardiovascular autonomic function tests. Results: At enrollment, patients were 68 ± 12 years old (median ± interquartile range) and had had autonomic failure for 5 ± 7 years. Within 4 years of follow‐up, 25 of 74 subjects (34%) developed dementia with Lewy bodies (n = 13), Parkinson disease (n = 6), or multiple system atrophy (n = 6). The presence of probable rapid eye movement (REM) sleep behavior disorder was strongly associated with the development of a manifest central nervous system (CNS) synucleinopathy (odds ratio = 7.1). Patients who phenoconverted to multiple system atrophy had younger age at onset of autonomic failure, severe bladder/bowel dysfunction, preserved olfaction, and a cardiac chronotropic response upon tilt > 10 beats per minute. Those who phenoconverted to Parkinson disease or dementia with Lewy bodies had decreased olfaction, a lesser chronotropic response to tilt, and a longer duration of illness. The small group of patients retaining the pure autonomic failure phenotype had very low plasma norepinephrine levels, slow resting heart rate, no REM sleep behavior disorder, and preserved smell. Interpretation: Patients presenting with pure autonomic failure are at high risk of phenoconverting to a manifest CNS synucleinopathy. Specific clinical features predict future diagnosis. Ann Neurol 2017;81:287–297